Modeling of thermal distribution on cryosurface for low temperatures - Olga Vorobyova; Dmitriy Sokolov; Yevgeniy Korshikov (Physical Sciences and Technology)
In this work, the temperature distribution on a cryosurface at low temperatures (from 300 to 80 K) was studied. This type of cooling surface is intended for experimental processes of deposition and cooling of inorganic compounds, which allows for further studies of their physicochemical properties and structure. Surface cooling to cryogenic temperatures was simulated, and the obtained temperature-time dependences were calculated using the finite element method. Liquid nitrogen, which boils at 77 K, was used to cool the cryopanel from room to cryotemperatures. The results of the simulation are presented for the temperature distribution during cooling across the volume and surface of the cryopanel. For comparison, the heat-conducting capacity of the material from which the cryopanel is made was studied and whether the material would affect its efficiency. In this case, the optimal surface temperature was reached after 800 seconds, while the liquid nitrogen passed through a coil with a diameter of 6 mm. Thus, the computer modeling method provides valuable recommendations for the design of efficient cryogenic surfaces.